A comparative assessment of competition in Africa: identifying drivers of reform in Botswana, Ethiopia, and Nigeria. (8th December 2017) - Dawar, Kamala; Ndlovu, Ndaba
Abstract: This article undertakes a comparative assessment of the development of competition in Botswana, Ethiopia, and Nigeria. These three African countries have all sought to introduce domestic competition law since 2000. The article identifies the different factors that have contributed to the relative success in introducing competition law in Botswana, as compared to both the Nigerian and Ethiopian experience. The article highlights the significance of both domestic and external factors in nurturing competition and good economic governance. It concludes that effective enforcement of competition law is founded on both internal and international dynamics. While domestic will for competition is a necessary precondition, the case of Botswana indicates how domestic reforms needed to be buttressed by capacity building and expertise from external sources, for the betterment of markets, producers, and consumers.